Optimization of Methodology for Rearing Spodoptera albula on Artificial Diet - Di Bello, M. M. [UNESP]; Souza, B. H.S.; Nogueira, L. [UNESP]; Ribeiro, Z. A. [UNESP]; Eduardo, W. I. [UNESP]; Boiça Júnior, A. L. [UNESP] (Springer Nature, 2017)
Advances in techniques for rearing insects on artificial diets are fundamental to solving issues of basic and applied entomology. In this study, we evaluated the development of Spodoptera albula (Walker) (Lepidoptera: Noctuidae) on three artificial diets used for other species of Lepidoptera, at three larval densities, and two densities of adult couples housed in oviposition cages of two sizes, with the aim of optimizing methodology for rearing S. albula in the laboratory. Biological parameters were recorded from S. albula, and a fitness index was calculated based on the larval survival and duration and weight of pupae. The total and daily oviposition was recorded using 5 or 10 adult couples of S. albula housed in two cage sizes. Concentrations of total nitrogen and protein in the tested diets were determined. Development of S. albula was completed in all artificial diets; however, the diet used for rearing Anticarsia gemmatalis (Hübner) larvae was the most suitable for S. albula, yielding intermediate development time and higher survival relative to the other diets. Individualization of larvae favored S. albula development by producing overall greater weights of larvae and pupae, higher survival rates, and longer adult longevity. Cage size and number of couples per cage did not influence S. albula fecundity in the experiment conditions. Spodoptera albula can be satisfactorily reared on the artificial diet used for A. gemmatalis, using one larva per tube, and either density of adults at any cage size. Additional amendments are needed in the rearing methodology to achieve optimal conditions for larval development to adulthood.
Keywords: Insect nutrition; insect rearing; larval density; oviposition cage; protein content